Early Vocal Development in Autism Spectrum Disorder, Rett Syndrome, and Fragile X Syndrome: Insights from Studies Using Retrospective Video Analysis - Roche, Laura (2018)
This article provides an overview of studies assessing the early vocalisations of children with autism spectrum disorder (ASD), Rett syndrome (RTT), and fragile X syndrome (FXS) using retrospective video analysis (RVA) during the first 2 years of life. Electronic databases were systematically searched and a total of 23 studies were selected. These studies were then categorised according to whether children were later diagnosed with ASD (13 studies), RTT (8 studies), or FXS (2 studies) and then described in terms of (a) participant characteristics, (b) control group characteristics, (c) video footage, (d) behaviours analysed, and (e) main findings. This overview supports the use of RVA in analysing the early development of vocalisations in children later diagnosed with ASD, RTT, or FXS and provides an in-depth analysis of vocalisation presentation, complex vocalisation production, and the rate and/or frequency of vocalisation production across the three disorders. Implications are discussed in terms of extending crude vocal analyses to more precise methods that might provide more powerful means by which to discriminate between disorders during early development. A greater understanding of the early manifestation of these disorders may then lead to improvements in earlier detection.